The development of local plants e-module based on mobile learning for the subjects of botany and plant morphology - Masing, Feliksitas Angel; Sila, Vinsensia Ulia Rita (Biosfer: Jurnal Pendidikan Biologi, 2023)
This research aims to know: 1) develop a local plant e module from Timor Tengah Utara Regency based on android mobile, 2) test the feasibility of a local plant e module from Timor Tengah Utara Regency based on android mobile on the aspect of substance/material and aspects of learning media. This type of research is development research using the Design and Development Research (DDR) method at the Validity stage which includes development, internal validation by material experts and learning media experts and external validation by third semester students of Biology Education Study Program, University of Timor as test participants. The results of this study are; 1) development of local plant modules from Timor Tengah Utara Regency based on mobile android in accordance with the Design and Development Research (DDR) development model at the Validity stage which includes development, internal validation, and external validation, 2) local plant modules from Timor Tengah Utara Regency based on android mobile is feasible to use in terms of substance/material and learning media. Based on the assessments of material experts and learning media experts, this module is in the "good" category, while the assessment by students as trial participants is in the "very good" category. The content of the E module is local plants originating from Timor Tengah Utara Regency which consists of several plants such as Santalum album, Pinus merkusii, Piper majusculum Blume, Coffea arabica, Arenga pinnata, Aleurites moluccana, Rhizophora apiculata, and so on. Each plant presented in the e module is equipped with its classification and morphology so that it is very useful for Biology students at the University of Timor in studying plant botany and morphology courses.